Analisis Faktor-Faktor yang Mempengaruhi Minat Mahasiswa Akuntansi Universitas Islam Malang Dalam Pengambilan Certified Public Accountant (CPA) - Putri, Via Karina; Sudaryanti, Dwiyani; Hidayati, Irma (Universitas Islam Malang, 2023)
This research was conducted to determine the factors that influence the interest of accounting students at the Islamic University of Malang in taking a Certified Public Accountant (CPA). This study uses the variables of quality motivation, economic motivation, costs, and career opportunities on the interest of accounting students at the Islamic University of Malang in taking a Certified Public Accountant (CPA). The research data was collected through a questionnaire to 167 respondents, based on the results of the slovin formula. The research method used is the method of multiple linear regression analysis with the help of the SPSS 25 program. This research was conducted because the increase in undergraduate accounting graduate students contrasted with the increase in the number of Public Accounting Firms (KAP), in practice the higher the level of economic actors in Indonesia, the awareness of the importance of public accounting services. According to the website (iaiglobal.or.id, 2022) the number of Public Accounting Firms (KAP) from 2018 to 2021 recorded an annual increase of only 1.28%. With an average number of 35,000 undergraduate accounting graduates, only 2.290 are recorded as having CPA certificates (Antares, 2019). Based on data from the Center for Development of Accountants and Appraisal Services (PPAJP), public accountants in Indonesia are very minimal when compared to neighboring countries. The public accounting profession in Indonesia from 2018 to 2021 recorded a growth of only 0.49% per year. The results showed that quality motivation, economic motivation, costs, and career opportunities had an effect on the interest of accounting students at the Islamic University of Malang in taking a Certified Public Accountant (CPA). Keywords: quality motivation, economic motivation, costs, career opportunities